Assessment of Child Immunization Coverage and Associated Factors with Full Vaccination among Children Aged 12–23 Months at Mizan Aman Town, Bench Maji Zone, Southwest Ethiopia. (24th December 2017) - Meleko, Asrat; Geremew, Mesfin; Birhanu, Frehiwot
Abstract : Immunization remains one of the most important and cost-effective public health interventions to reduce child mortality and morbidity. Globally, it is estimated to avert between 2 and 3 million deaths each year. In Ethiopia, immunization coverage rates stagnated and remained very low for many years. Thus, this study was aimed to assess child immunization coverage and factors associated with full vaccination among children aged 12–23 months in Mizan Aman town. The study design was community-based cross-sectional survey. Data was collected by using pretested structured questionnaire. A total of 322 mothers/caretakers were interviewed. Based on vaccination card and mothers/caretakers' recall, 295 (91.6%) of the children took at least a single dose of vaccine. From total children, 27 (8.4%) were not immunized at all, 159 (49.4%) were partially immunized, and 136 (42.2%) were fully immunized. Mothers/caretakers educational level, fathers' educational level, place of delivery, maternal health care utilization, and mothers/caretakers knowledge about vaccine and vaccine-preventable disease showed significant association with full child immunization. The finding from this study revealed that child immunization coverage in the studied area was low. Thus the town health office and concerned stakeholders need to work more to improve performance of the expanded program on immunization in this area.